Value orientations in professional training of teacher-educators - Пріма, Раїса Миколаївна; Prima, Raisa M. (My University, 2014)
Highlights some aspects of scientific and organizational support axiological orientations in the training of future teachers as educators translator value paradigm, a leading educational strategy. Attention is focused on the analysis of its theoretical and methodological foundations through the disclosure of the substantive nature of the dominant concepts - "value", "axiosphere personality", "principles of axiological approach" to training future teachers-educators. The basis of axiological priorities support actively stimulating the professional and pedagogical preparation of present teacher educators is the system of principles: the principle of the value-based orientations interiorization reflecting the theory ideas of pedagogical axiology; the principle of humanistic orientation of professional preparation, value-targeted attitude toward professional activity accumulating the realization of the axiology approach in professional preparation of future teacher educators; and the principle of interdisciplinary as the reflection of general pedagogical principles of professional preparation.
Keywords: values; axiological approach; the future teacher-educator; professional training; wartości; aksjologiczne podejście; nauczyciel-wychowawca w przyszłości; szkolenie zawodowe